Rice Seed Business Development Strategy Using SWOT and QSPM at UD. Sritanjung, Pondoknongko Village, Kabat District, Banyuwangi - Hanry Wiratmoko; Rizal; Dadik Pantaya (Jurnal Manajemen Agribisnis dan Agroindustri)
Rice is the leading food commodity in Banyuwangi Regency. The development of rice food crops cannot be separated from the availability of quality rice seeds. UD. Sritanjung is a business entity that operates in the field of rice seed breeding to provide quality rice seeds, especially in Banyuwangi Regency. Development of rice seed business at UD. Sritanjung needs to be implemented to support the development of rice food commodities in Banyuwangi Regency. This research aims to design a strategy based on UD's internal and external environmental conditions. Sritanjung Banyuwangi. This research is classified as quantitative descriptive research using the SWOT and QSPM methods. SWOT analysis is aimed at obtaining the best strategic alternatives, while QSPM analysis is carried out to rank these alternative strategies based on strategic priorities. The results of the research show that there are five alternative strategies produced, namely: 1) increasing the quantity of seed product production, especially seeds with high sales, 2) improving the quality of rice seeds produced through certification of new products and products that have not been certified, 3) opening shops in various existing marketplaces such as Tokopedia, Shopee, Lazada, Bukalapak, JD.id, and other marketplaces, 4) increasing promotion of certified rice seeds inside and outside the city directly, and 5) collaborating with the Banyuwangi Regency Government. The priority strategy in this research is to directly increase the promotion of certified rice seeds inside and outside the city.